2003
DOI: 10.1002/rcm.940
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for fabrication of silver‐coated sheathless electrospray emitters

Abstract: A simple and time-saving procedure is proposed for preparing a silver-coated fused-silica capillary tip. The tapered capillary tip was coated with silver using an acrylic-based silver conductive pen. The fabrication of a silver-coated fused-silica capillary tip takes less than 5 minutes. The silver-coated fused-silica capillary tip is rugged and durable for sheathless capillary electrophoresis/electrospray mass spectrometry and also for microspray applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In its most recent version, CE capillary is carefully sharpened, i.e., by etching the outer capillary wall with hydrofluoric acid (HF) [44,88,[104][105][106] or mixtures of sulfuric and phosphoric acid [90], by mechanical shapening with an abrasive, by flameor laser-heated pulling [88,[107][108][109][110] or a combination of several techniques [37]. Kriger et al [109] reported a further cleaning subsequent to capillary sharpening by means of a so-called "piranha solution" (mixture of H 2 O 2 and sulfuric acid).…”
Section: Sheathless Interface (Nanospray)mentioning
confidence: 99%
“…In its most recent version, CE capillary is carefully sharpened, i.e., by etching the outer capillary wall with hydrofluoric acid (HF) [44,88,[104][105][106] or mixtures of sulfuric and phosphoric acid [90], by mechanical shapening with an abrasive, by flameor laser-heated pulling [88,[107][108][109][110] or a combination of several techniques [37]. Kriger et al [109] reported a further cleaning subsequent to capillary sharpening by means of a so-called "piranha solution" (mixture of H 2 O 2 and sulfuric acid).…”
Section: Sheathless Interface (Nanospray)mentioning
confidence: 99%
“…A sheath or make-up flow [5][6][7] can be used to mix with the CE effluent at the outlet to establish the electrical contact. While for sheathless interfaces the electrical contact was established by direct application of high voltage (HV) via a conductive coating at the capillary tip, [8][9][10][11] through a liquid junction by inserting a narrow metal wire into the capillary outlet or utilization of a stainless steel tip, [12][13][14][15] or just through the CE high voltage. [16][17][18] However, problems such as coating damage and formation of air bubbles [19] may occur at the physical interface between the electrode and the buffer solution.…”
Section: Methodsmentioning
confidence: 99%
“…In this approach, conductive rubber instead of carbon coating [10] or silver coating [24] was used to coat the tip. The conductive rubber kit which is often used in repairing and modifying printed circuits was used to coat the sprayer.…”
Section: Conductive Rubber Coatingmentioning
confidence: 99%
“…However, resolution may somewhat degrade because of the production of the laminar flow in a pressure-driven system [30,31]. Another strategy, which is often adopted, is the use of a tapered tip with 20 mm or less od [22][23][24][25]. Nevertheless, the susceptibility to breaking or clogging of the tip during coating or sample analysis limits the application of tapered tips having small orifices [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation